Evaluarea actului de guvernare la nivel local din perspectiva bunei guvernări - Ionuţ Cătălin Hădadea; Călin Emilian Hinţea (Revista Transilvană de Ştiinţe Administrative, 2018)
The present study represents an ambitious attempt of evaluating the existing governance in the Romanian municipalities of above 50,000 inhabitants, from the perspective of good governance. This subject is of interest for administrative science, as science contributes to generating good governance principles, but also the optimum conditions for its deployment. On the basis of the principles of local autonomy and decentralization, local public authorities are able to manage local affairs on their own budget and on their own local regulations. Moreover, local authorities have means for encouraging active citizenship and the private domain. Knowledge about the quality of local governance in the economic, social and political context plays an important role in decision making for potentially external economic promoters. At the same time, it is an important tool for identifying strong assets for community development and strategic planning. Evaluating the quality of governance might lead to finding problems regarding the relationship between civil society and the local public authorities, and the study of good governance contributes to the improvement of this relationship and public perceptions over the institutions.